Volume 8: Ocean Renewable Energy 2013
DOI: 10.1115/omae2013-10244
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Pitch Decay of a Floating Offshore Wind Turbine Structure

Abstract: Model tests were conducted on three generic floating wind turbine systems in 2011, and reported in a series of papers at OMAE 2012. These tests were conducted at the MARIN facility in the Netherlands, by a consortium of universities, government research organizations and industry. As part of the testing program, decay tests in platform pitch were conducted with and without wind. It was found that for spar and semi-submersible type structures, resonant pitch motion was damped due to wind in storm sea conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is found that the second-order forces were small for the OC3-Hywind spar, but clear second-order LF responses were seen, due to the wave excitation at resonant frequencies. Thiagarajan et al (2013) studied the nonlinear decay motion of a spar FOWT and compared with model test results. In particular, the nonlinearity of the pitch motion is analyzed in detail in the study.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the second-order forces were small for the OC3-Hywind spar, but clear second-order LF responses were seen, due to the wave excitation at resonant frequencies. Thiagarajan et al (2013) studied the nonlinear decay motion of a spar FOWT and compared with model test results. In particular, the nonlinearity of the pitch motion is analyzed in detail in the study.…”
Section: Introductionmentioning
confidence: 99%